Evaluación Del Tráfico Vehicular Para Conocer El Nivel De Servicio De La Avenida Francisco De Orellana, En El Tramo Desde La Avenida Miguel H. Alcívar Hasta La Calle José Santiago Castillo, Ubicada En La Parroquia Tarqui Del Cantón Guayaquil, Provincia Del Guayas. - Cabeza Quintero, Gissela Amanda (2016)
pdf